Modéliser les processus de collaboration entre acteurs de l’éducation et de la recherche pour la construction de savoirs - Aldon, Gilles; Monod-Ansaldi, Réjane; Nizet, Isabelle; Prieur, Michèle; Vincent, Caroline (Nouveaux cahiers de la recherche en éducation, 2020)
Les recherches en éducation s’enracinent profondément dans la réalité complexe des phénomènes d’enseignement et d’apprentissage, convoquant les acteurs de la recherche et de l’éducation à appréhender cette complexité dans un travail commun. L’inscription de ce travail dans une perspective participative ou collaborative nécessite une intelligibilité accrue des processus collaboratifs à l’oeuvre et des défis qu’ils posent aux différents acteurs. Nous proposons dans cet article un modèle théorique des processus de collaboration fondé sur une construction épistémologique et méthodologique croisant des cadres théoriques issus de l’anthropologie, de la psychologie, de la philosophie, de la didactique et des sciences du langage, avec pour ambition de créer une meilleure intelligibilité des processus à l’oeuvre dans les recherches participatives en éducation.
Keywords: Négociation; Participation; Recherche collaborative; Réservé UdeM; Sciences de l'éducation

TRIZ for Shaping Life-Long Learning - Pariyar, Amit; Kulathuramaiyer, Narayanan; Bala, Poline; Man, Chuah Kee (2020 IEEE 8th R10 Humanitarian Technology Conference (R10-HTC), 2020)
The dependence on digital technologies has seen a significant increase during COVID-19 pandemic, to ensure that social connectivity and work goes on, in spite of lockdowns and the physical controls on movement. Though digital learning is expected to create abundant life-long learning opportunities for learners worldwide in this challenging time, there is a danger to further impose inequalities and inadequate access to quality education and life-long learning for the unconnected or poorly connected population. This paper shares our experience of reengineering a MOOC platform as `Community led MOOCs' to serve the learning needs of most under represented single mother communities in Bario - a remote settlement of Kelabits in the Borneo Island of Malaysia. This paper then explores TRIZ based heuristic models to address the socio-technological barriers to lifelong learning and proposes TRIZ principles that can trigger social innovation and creativity in designing lifelong learning solutions for rural communities.
Keywords: Asie; Internet; MOOC; Objectifs de développement durable; Participation; Réservé UdeM; Technologies; Théorie de Résolution des Problèmes Inventifs (TRIZ); numérique

Strengthening social innovation in higher education institutes - an organizational change process involving staff and students - Prantl, Judith; Freund, Susanne; Kals, Elisabeth (Social Enterprise Journal, 2021)
Purpose In recent decades, higher education institutes (HEIs) have come under pressure to cooperate with society as a whole. This shift towards an increased focus on third mission and social innovation activities implies a substantial organizational change process for many HEIs, as they need to initiate both structural and cultural changes. This paper provides guidance for such change processes by examining the views and attitudes of academic and administrative staff, as well as students within the HEIs over a period in which the HEIs increase their focus on social innovation. Design/methodology/approach The study uses a longitudinal quantitative approach consisting of a survey of administrative and academic staff, as well as students at two German HEIs. The authors studied members' attitudes towards third mission and social innovation activities (N = 3470). Findings Results suggest that the university members' attitudes towards third mission and social innovation are positive but change to some extent over time. Different aspects shape the attitudes within the three groups (administrative staff, academic staff and students). Furthermore, attitudes vary among academic employees who are involved in the process and those who are not. Practical implications The findings provide useful information for university managers and anyone aiming to promote social innovation at HEIs. Originality/value The study examines how attitudes of university members change whenever social innovation takes place at HEIs. This study includes data on the participation and empowerment of all HEI members in view of the important role that HEIs can play as supporters of social innovation.
Keywords: Innovation sociale; Rôle des universités; Université

From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Springer International Publishing, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
Keywords: Europe; Rôle des universités

Integrating Social Innovation into the Curriculum of Higher Education Institutions in Latin America: Insights from the Students4Change Project - Unceta, Alfonso; Guerra, Igone; Barandiaran, Xabier (Sustainability, 2021)
In the last two decades, social innovation (SI) and social entrepreneurship (SE) have gained relevance and interest within the framework of academia at international level. Higher education institutions (HEIs) are key players in promoting innovation and social entrepreneurship initiatives that respond to multifaceted challenges. They support strategies on the basis of the strengthening of participation, collaboration, and cooperation with society and its local communities. However, the approach of Latin American universities to SI and SE has been very uneven in the way they have understood them, integrated them into academic programmes, and transferred knowledge to society. On the basis of the experience of the Students4Change project, we sought to understand the role of Latin American HEIs in promoting social innovations by analysing the experiences of 10 participating universities to formalise a pedagogical programme on SI and SE in their institutions. The results suggest that there is still a need to formalise an academic syllabus that is speciﬁcally designed to promote social innovations and to train universities in this endeavour. This paper contributes to the identiﬁcation of the main levers of change, strengths, and challenges that Latin American universities face to institutionalise SI and SE in their contexts.
Keywords: Amérique latine; Libre accès; Rôle des universités

The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Keywords: Europe; Réservé UdeM; Rôle des universités

Decentering social innovation: the value of dispersed institutes in higher education - Lough, Benjamin J. (Social Enterprise Journal, 2021)
Purpose – This paper aims to illustrate how dispersed institutes of social innovation operating as intermediary actors within higher education institutions (HEIs) may help overcome many of the institutional bureaucracies and structures that inhibit social innovation in higher education.
Keywords: Version libre-accès ResearchGate

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
Keywords: Europe; Rôle des universités

Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Keywords: Europe; Libre accès; Rôle des universités

Digital Innovation during COVID-19: Transforming Challenges to Opportunities - Yu Chen; Roldan, Malu (Communications of the Association for Information Systems, 2021)
The coronavirus disease of 2019 (COVID-19) swiftly changed almost all aspects of our lives and society. In this paper, we depict course adjustments that we made to an undergraduate digital innovation course project, called Innovation Farm (IF), in response to the pandemic. Designed as an in-person course project, IF requires students to create AIpowered Android apps to address important social issues. As stay-at-home orders came into effect in March, 2020, we shifted the course to the online modality refocused its student topics to address social issues that COVID-19 has engendered. Accordingly, we also discuss three challenges that we faced and the strategies we employed to cope with them; namely, framing students' social innovation topics in the COVID-19 context, using virtual studios for online groupwork, and hosting a virtual pitch competition. Surprisingly, these strategies not only addressed the challenges but also created unintended benefits and opportunities. We hope to encourage educators to consider the possibilities in transforming challenges to opportunities during these unprecedented times.
Keywords: Réservé UdeM; Rôle des universités; États-Unis

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique

Unpacking Formation Mechanisms of Social Innovation Initiatives in Cuernavaca, Mexico - Lüken, Harmke Jan; Zapf, Jan (Malmö University, 2021)
This study seeks to unpack the formation mechanisms of social innovation (SI) initiatives in Cuernavaca, Mexico. Subsequently, this study employs a qualitative case study to investigate (1) local embedding, (2) trans-local connectivity and (3) university linkages of SI initiatives in Cuernavaca. Previous research indicated that socio-spatial dynamics are critical for the development of SI initiatives. Furthermore, previous research asserted that universities are imperative to SI in the context of Latin America. Nevertheless, previous research contemplating the formation mechanisms of SI was primarily westerncentric and displayed an inadequacy to acknowledge SI in the context of Latin America. Based on previous research this study presents a theoretical framework that classifies the results in eight typologies based on (1) local embedding, (2) trans-local connectivity and (3) university linkages. All three dimension are classified as either "high" or "low", which grants insights into influential formation mechanisms. Subsequently, a sample of n=10 SI initiatives was compiled and twelve semi-structured interviews with representatives of the SI initiatives were conducted. The results indicate three typologies of SI initiatives. Five SI initiatives were classified as: HLH – high local embedding, low trans-local connectivity, and high university linkages. Four initiatives were classified as: LHH – low local embedding, high trans-local connectivity, and high university linkages. One initiative was classified as HLL – high local embedding, low trans-local connectivity, low university linkages. The results indicate that SI initiatives either seek to address local challenges or direct their efforts to trans-local challenges. Furthermore, universities evidently play a critical role in the formation of SI initiatives in Cuernavaca and Mexico. This study contributes to SI literature by presenting evidence that universities possess critical roles in the formation of SI. Future research should increasingly embed universities into theoretical approaches when investigating SI formation mechanism in Latin America.
Keywords: Amérique latine; Libre accès

Transformational spaces: educators discuss map the system and supporting Canada’s emerging generation of systems thinkers - McGowan, Katharine; Calf Robe, Latasha; Allan, Laura; Bray-Collins, Elinor Flora; Couture, Mathieu; Croft, Sarah; Daling, Antonio; Farahbakhsh, Amy; Grossman, Susan; Hassan, Sara; Heidebrecht, Paul; Helwig, Nicole; et al. (Social Enterprise Journal, 2021)
The purpose of this paper is to explore multiple Canadian educators' experiences with the Map the System (MTS) competition, designed to foster and grow systems thinking capacity among students exploring complex questions. The challenge has been an opportunity for social innovation programs (from the nascent to the established) across Canadian post-secondaries to engage both with their own communities and with social innovators internationally, connecting social innovation spaces as part of their third mission. Across the organizations, students valued the interdisciplinary and systems thinking qualities, and organizations benefited from the external competition, there remain questions about organizational engagement in social innovation as a deeply transformative process internally. Design/methodology/approach All Canadian post-secondary institutions who participated in the 2020 MTS competition (17) were invited to a digital roundtable to discuss their experiences. Ten were able to participate, representing a range of post-secondaries (including large research institutions, undergraduate-only universities and colleges). To facilitate discussion, participants met to discuss format and topics; for the roundtable itself, participant educators used a google form to capture their experiences. These were summarized, anonymized and redistributed for validation and clarification. To reflect this collaborative approach, all participant educators are listed as authors on this paper, alphabetically after the organizing authors. Findings For students participating in MTS, they have built both their interdisciplinary and systems thinking skills, as well as their commitment to achieving meaningful change in their community. But MTS arrived in fertile environments and acted as an accelerant, driving attention, validation and connection. Yet while this might align with post-secondary education’s third mission, educators expressed concerns about sustainability, internal commitment to change and navigating tensions between a challenge approach and collaborative work, and internal work and national competition limitations. This complicates the simple insertion of MTS in a post-secondary’s social innovation-related third mission. Research limitations/implications This study was limited to Canadian post-secondaries participating in MTS, and therefore are not representative of either post-secondaries in Canada, or all the MTS participants although Canada is well represented in the challenge itself. Additionally, while the authors believe their approach to treat all participants as authors, and ensured multiple feedback opportunities in private and collectively, this is a deliberate and potentially controversial move away from a traditional study. Social implications More than half of Canadian universities (a subgroup of post-secondaries) had at least one social innovation initiative, but questions have been raised about whether these initiatives are being evaluated internally, or are triggering the kinds of transformative internal work that might be an outcome. Understanding the impact of MTS one example of a social innovation-related initiative can help advance the broader conversation about the place (s) for social innovation in the post-secondary landscape – and where there is still significant work to be done. Originality/value As Canada has only participated in MTS for four years, this is the first inter-institution consideration of its related opportunities and obstacles as a vehicle for transformational social innovation. As well, educators talking openly and frankly to educators reinforces the collaborative quality of social innovation across the post-secondary landscape.
Keywords: Canada

Engineering education through social innovation: the contribution of professional societies - Gorham, Douglas; Nwulu, Nnamdi (Lecture notes in networks and systems, 2020)
This book explores the nexus between professional technical societies and engineering education by examining several societies' efforts to promote and support engineering and engineering education in the areas of pre-university education, university education and informal education through programs and activities designed to leverage social innovation. Professional societies are in a unique position to support and contribute to engineering education, and have dedicated substantial resources to social responsibility programs and activities that promote engineers and engineering. The book is chiefly intended for engineers, engineering educators, staff members of professional technical societies, and for the broad range of scholars whose work involves technology education and education policy.
Keywords: Réservé UdeM

New Challenges in Universities: Teaching Social Entrepreneurship - Lam-Lam, Suisin; Ahumada-Tello, Eduardo; Plascencia-López, Ismael; Ovalle-Osuna, Oscar Omar; Virginia Barragán-Quintero, Reyna; Evans, Richard David; Soria-Barreto, Karla (2019 IEEE Technology Engineering Management Conference (TEMSCON), 2019)
This study analyses the importance of teaching social entrepreneurship in state universities. A survey was applied to university students to find out if personality traits are related to the characteristics of social entrepreneurship. This was achieved through Alpha Cronbach and Pearson/Spearman correlation analysis. The results show that students have the personality traits to become social entrepreneurs. However, social entrepreneurship courses are not taught in universities of Tijuana city. Therefore, it is strongly suggested to teach social entrepreneurship in universities of the city and the state because students possess social entrepreneurship traits and are interested in the subject.
Keywords: Amérique latine; Réservé UdeM; Rôle des universités

Utilizing Crowdsourcing in Education: Academic Retiree and Professional Continuity - Raus, Mohd. Ikhsan Md.; Supian, Suzaini Harmiruslin; Zolkefley, Mohd Khairul Ikhwan Bin; Aziz, Muhd Eizan Shafiq Abd (Springer, 2019)
The socioeconomic challenges caused by aging populations have encouraged many countries to reevaluate the place of the elderly in society as well as to adopt measures in encouraging them to be participative. In recent decades, crowdsourcing has been identified as a rapid growth of innovative Internet-based information and communication technologies in giving the opportunities to educational organizations to reach their goals. With their accumulated skills and knowledge, academic retirees can be resourceful to society. However, their knowledge and experiences seem to be undervalued and underutilized. Retired academics have better opportunity to extend their contribution in the society as their valuable knowledge is more appreciated than people from other background. Retired academics tend to be able to fulfill their desire for professional continuity following retirement more markedly than people from other backgrounds. This paper analyzes the use of crowdsourcing in educational activities, especially for the academic retirees. Therefore, the objectives of this paper are to take an exploratory look on how educational organizations use crowdsourcing as part of their activities at the present time, and to suggest how the practice of crowdsourcing may expand to other educational activities in future.
Keywords: Asie; Réservé UdeM

Empowering social innovators through collaborative and experiential learning - Pappas, Ilias O.; Mora, Simone; Jaccheri, Letizia; Mikalef, Patrick (2018 IEEE Global Engineering Education Conference (EDUCON), 2018)
Educating social innovators in higher education is of great importance as many societal challenges exist. This study combines experiential learning with ICT tools to provide students with the needed competences and experiences to solve societal challenges. We employ this approach in an innovative course, named Experts in Teamwork (EiT), which follows the experiential learning cycle. The participants of this study are undergraduate students interested to learn how they can solve societal challenges. Specifically, 26 students with various background and nationalities participated. A collaborative platform was developed that supports teamwork and cooperation, as well as the social innovation process. The findings show that this approach can influence positively learning outcomes and increase students' engagement and motivation with both social innovation and the learning process. Also, students' creativity was increased leading to the development of better solutions. The overall outcomes contribute to theoretical and practical development, to allow educators to take appropriate measures to enhance students' learning experience and foster social innovation through ICT.
Keywords: Réservé UdeM; Rôle des universités

Toward the Practice of Social Innovation for the Common Good: An Integration of “Teaching-Research-Service” - Han, I.; Hou, Sheng-Tsung (Social Innovation and Business in Taiwan, 2016)
“Many suppliers and users of social research are dissatisfied, the former because they are not listened to, the latter because they do not hear much they want to listen to” (Lindblom & Cohen, 1979: 1). As mentioned in Chapter 1 of this book, the recent events of global financial crisis and a series of Occupy Wall Street protests have raised reflections of business management education on MBA trainings. The question of whether management research and education can be a facilitator toward events that would eventually destroy the world economy or a facilitator toward achieving social value and human glory has been raised with those reflections. MBA graduates should not be used as profiting tools for big corporations anymore. Moreover, the separation between management theory and industry practice has, for a long time, caused a dilemma with regard to the difficulties inherent in dialogue between academia and industry. There have been urgent calls to embody management research into applicable industry knowledge in order to minimize the gap in between the two (Anderson, Herriot, & Hodgkinson, 2001; Rynes, Bartunek, & Daft, 2001; Van de Yen & Johnson, 2006).
Keywords: Asie; Réservé UdeM

Education and Social Innovation - Rasmussen, Palle (Encyclopedia of Educational Innovation, 2019)
The idea of social innovation has become increasingly popular in recent years, and as often happens with popular concepts it risks become overloaded. This happens, for instance, when social innovation is seen as the “soft” and humanistic alternative to versions of innovation dominated by science and technology. There has been a fast growing literature on social innovation, some of it in academic publications but perhaps most of it published by think tanks, semigovernmental agencies, and other organizations. Many different institutional fields for social innovation are discussed in the literature (Moulaert et al. 2013). Education is one of them, but much less frequently treated than fields like housing, intercultural relations, environmental issues, and childcare.
Keywords: Ouvrages de référence; Réservé UdeM; Sciences de l'éducation